The whole world's crazy - Gownley, Jimmy (New York : Ibooks : Distributed by Simon & Schuster, 2003)
These all-ages color stories about a girl and her group of friends are funny and touching with enough bite to keep them from being too "kiddy." Amelia's parents have just gotten divorced, and she and her mom have moved in with her Aunt Tanner. Like many kids, she sees herself as the only normal one, surrounded by crazy friends and relatives. She hangs out with a varied group of misfits-some of who really are weird, like Pajamaman, a kid who never speaks or changes out of his sleepwear-to avoid thinking about the trauma she's facing at home. Many of the stories are linked, connected by short monologues in which Amelia explains more about her situation, the characters, or how she feels. These kids are real-that means that sometimes they're evil, greedy, and self-centered. Sometimes they don't understand or see things that are obvious to us, and when they do notice, it's the biggest thing in the world to them. That vision is an eye-opener for the reader, and Jimmy Gownley is a genius at capturing their perspective. These kids are realistic while still being sympathetic and even funny.
13 29
Keywords: Comic books, strips, etc. -- United States; McBride, Amelia Louise (Fictitious character); Fourth grade -- Comic books, strips, etc; Schools -- Comic books, strips, etc; Cartoons and comics; Comic books, strips, etc. -- United States